Ecology and Recovery of Eastern Old-Growth Forests (Island Press/Center for Resource Economics, 2018)
"An important contribution to the burgeoning literature extolling the virtues of forest complexity. As a compendium of the literature on forest heterogeneity alone, this book is an indispensable reference for scholars and practitioners of ecological forest management." Gregory H. Aplet, Senior Science Director, The Wilderness Society "Ecology and Recovery of Eastern Old-Growth Forests is extremely timely and hugely important. Old-growth forests are quickly disappearing, and global changes mandate that we find new approaches to manage them. Succinctly written by prominent American and Canadian scientists, this book is a must-read for forest professionals and enthusiastic forest lovers everywhere." Christian Messier, Professor of Forest Ecology, Université du Québec à Montréal and Université du Québec en Outaouais "Finally, a much-needed, up-to-date treatise on the state of old-growth forests in the East. All forest stakeholders should read this book." Jerry F. Franklin, Professor Emeritus, University of Washington .